When assessment defines the content—understanding goals in between teachers and policy. Issue 2 (24th July 2020) - Mølstad, Christina Elde; Prøitz, Tine S.; Dieude, Alessandra
Abstract : Education policy development internationally reflect a widespread expansion of learning outcome orientation in policy, curricula and assessment. In this paper, teachers' perceptions about their work are explored, as goals and assessment play a more prominent role driven by the introduction of a learning outcomes‐oriented system. This is investigated through interviews of Norwegian teachers and extensive policy analysis of Norwegian policy documents. The findings indicate that the teachers are finding ways to negotiate and adjust to the language in the policies investigated in this study. Furthermore, the findings show that the teachers have developed their professional language according to the policies. The teachers referred to their self‐made criteria and goal sheets as central tools in explicating what is to be learned. In many ways, the tools for assessment, thus determine the content of education as well as what is valued in the educational system.